Unlocking the secrets of aortic pseudoaneurysms - exploring tensile testing of prostheses, anastomoses, and native vessels in the thoracic aorta: A clinical-engineering correlation - Recicarova, Sandra; Chlup, Hynek; Jonak, Michael; Netuka, Ivan (Journal of applied biomedicine, 2025)
INTRODUCTION: This study examines the mechanical properties of thoracic aortic false aneurysms (TAFA) and how the use of vascular prostheses, native vessels, and anastomoses affects their development. This is done through tensile testing, simulating a Bentall procedure, which is the most common surgery leading to TAFA development. METHODS: We conducted uniaxial tensile tests on the native right and left coronary arteries from five cadaveric donors. They were anastomosed to two vascular prostheses in the longitudinal and circumferential directions to assess their mechanical responses under load. RESULTS AND DISCUSSION: All anastomosis specimens ruptured on the native vessel side, with no breaches occurring on the prosthesis side. The P2 prosthesis exhibited a mechanical response closer to that of the native vessel compared to the P1 prosthesis. There were no statistically significant differences in wall thickness or mechanical properties between the left and right coronary artery samples, leading to the merging of these groups. The strain of the anastomosis in the longitudinal direction was significantly higher than in the circumferential direction. In both directions, the strain at the onset of rupture was greater than that of the native vessel, with a particularly notable difference in the longitudinal direction. Although there was no significant difference in stress values between the longitudinal and circumferential directions, forces per suture were slightly higher in the circumferential direction. CONCLUSION: Using the "endo-button buttress technique" with a double-layer anastomosis can help distribute the load and reduce stress. An alternative option is to use a Carrel patch to reinforce the connection between the target site and the conduit. Additionally, autologous pericardium can be employed for reinforcement.
Keywords: Cadaver; Male; koronární cévy; lidé středního věku; Stress, Mechanical; Bentall procedure; Coronary Vessels; pevnost v tahu; Humans; cévní protézy; Tensile testing; Middle Aged; mrtvola; senioři; Thoracic aortic false aneurysm; aorta thoracica; mužské pohlaví; Female; anastomóza chirurgická; Blood Vessel Prosthesis; Aged; nepravé aneurysma; mechanický stres; ženské pohlaví; Aneurysm, False; Tensile Strength; Aorta, Thoracic; Coronary arteries; aneurysma hrudní aorty; Aortic Aneurysm, Thoracic; Aortic pseudoaneurysm; Anastomosis, Surgical; lidé